Neutrophil extracellular traps in central nervous system pathologies: A mini review - Shafqat, Areez; Noor Eddin, Ahmed; Adi, Ghaith; Al-Rimawi, Mohammed; Abdul Rab, Saleha; Abu-Shaar, Mylia; Adi, Kareem; Alkattan, Khaled; Yaqinuddin, Ahmed (Frontiers in Medicine, 2023)
Neutrophils are rarely found in the brain because of the blood-brain barrier (BBB), but several diseases disrupt the BBB and cause neuroinflammation. In these settings, neutrophils adhere to the cerebral vasculature and transmigrate into the brain parenchyma. Neutrophils contribute to host defense through phagocytosis, degranulation, and neutrophil extracellular traps (NETs). However, NETs contain various cytotoxic proteases and pro-inflammatory constituents that exert significant collateral tissue damage. Recent studies show that NETs can disrupt the BBB, worsen neuroinflammation, and thereby exert neurotoxic effects. NETs have indeed been visualized in the brain after various insults, including traumatic (traumatic brain injury and spinal cord injury), infectious (bacterial meningitis), vascular (ischemic stroke), autoimmune (systemic lupus erythematosus), neurodegenerative (multiple sclerosis and Alzheimer’s disease), and neoplastic (glioma) causes. Significantly, preventing neutrophil trafficking into the central nervous system or NET production in these diseases alleviates brain pathology and improves neurocognitive outcomes. This review summarizes the major studies on the contribution of NETs to CNS disorders.